Negative electrode material with controllable metal loading depth, preparation method of negative electrode material and lithium metal battery

By preparing a negative electrode material with a controllable metal load depth, and using polyimidic acid nanofiber membrane for surface hydrolysis and chemical reactions, the problems of stability and cycle life of metal lithium anode materials in lithium metal batteries are solved, and the uniform diffusion of lithium ions and battery performance are achieved.

CN119695164AActive Publication Date: 2025-03-25NANJING UNIV OF AERONAUTICS & ASTRONAUTICS +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411782218.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-25
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The stability and cycle life of metal lithium anode materials in lithium metal batteries lead to complex diffusion paths of lithium ions, increasing the internal resistance of the battery and reducing electrochemical performance.

Method used

By preparing a negative electrode material with a controllable metal load depth, polyimidic acid nanofiber membrane is used to perform surface hydrolysis in alkaline solution and chemical reactions in metal salt solution to form stable chemical bonding to achieve uniform loading of metal particles.

Benefits of technology

It significantly reduces the lithium ion diffusion path, improves the charging and discharging performance and cycle stability of lithium metal batteries, and enhances the safety and reliability of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695164A_ABST
    Figure CN119695164A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium metal batteries, and particularly relates to a negative electrode material with controllable metal loading depth, a preparation method of the negative electrode material and a lithium metal battery. The preparation method of the negative electrode material with the controllable metal loading depth comprises the following steps: 1) carrying out electrostatic spinning on a polyamide acid solution, and carrying out heat treatment and annealing on an obtained membrane to prepare a nanofiber membrane; (2) soaking the nanofiber membrane in an alkaline solution for 0.5-3 hours, then putting the nanofiber membrane into a salt solution, soaking at 25-45 DEG C for 10-50 minutes, and drying; and (3) treating the nanofiber membrane dried in the step (2) for 0.5-24 hours at the high temperature of 200-3000 DEG C in an inert atmosphere to obtain the lithium metal battery. The preparation method disclosed by the invention can be used for realizing efficient exposure of a metal compound, remarkably promoting the performance of the lithium metal battery, greatly shortening the diffusion distance of lithium ions between an electrolyte and a negative electrode material, and strengthening the conductivity and the structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular, relates to a negative electrode material with controllable metal loading depth, a preparation method thereof, and a lithium metal battery. Background Art

[0002] With the rapid development of portable electronic devices and electric vehicles, the demand for high energy density batteries is growing. Lithium metal batteries have attracted much attention due to their high theoretical energy density, but the stability and cycle life of metal lithium anode materials need to be urgently addressed.

[0003] In order to improve the stability of lithium metal, researchers have explored a variety of methods, including designing functional electrolytes, coating artificial protective layers, designing high surface area current collectors, and loading lithium-philic substrates to reduce local current density and avoid the growth of lithium dendrites. The above methods are effective to a certain extent, but for embedded lithium-philic substances, the tortuous diffusion path will increase a certain diffusion barrier.

[0004] Therefore, developing a negative electrode material that efficiently utilizes the active matrix and shortens the diffusion distance of lithium ions is of great significance for improving the safety and electrochemical performance of lithium metal batteries. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a negative electrode material with controllable metal loading depth, a preparation method thereof, and a lithium metal battery.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a negative electrode material with controllable metal loading depth comprises the following steps:

[0008] 1) electrospinning a polyamic acid solution, and heat treating and annealing the obtained membrane to obtain a nanofiber membrane;

[0009] 2) soaking the prepared nanofiber membrane in an alkaline solution for 0.5-3 hours, then soaking it in a salt solution at 25-45°C for 10-50 minutes, and drying it;

[0010] The salt solution is a solution of one or more of metal hydrochloride, metal nitrate, metal sulfate, and metal carbonate;

[0011] 3) The nanofiber membrane obtained by drying in step 2) is treated at a high temperature of 200-3000° C. for 0.5-24 h under an inert atmosphere to obtain the nanofiber membrane.

[0012] The solvent of the polyimide acid solution in step 1) is at least one of distilled water, ethanol, acetone, dimethylformamide, dimethylacetamide, hexafluoroisopropanol, trifluoroacetic acid, tetrahydrofuran, acetic acid, dichloromethane, chloroform, etc. Preferably, the solvent is at least one of dimethylformamide, dimethylacetamide, hexafluoroisopropanol, and chloroform.

[0013] The mass concentration of the polyimide acid solution in step 1) is 1-50wt%, preferably, the mass concentration of the solution is 20-40wt%.

[0014] In step 1), the voltage of electrospinning is 1-30 kV, the receiving distance is 1-30 cm, the flow rate of the spinning solution is 0.1-20 mL / h, and the spinning time is 0.5-48 h. Preferably, the voltage of electrospinning is 15-25 kV, the receiving distance is 10-15 cm, the flow rate of the spinning solution is 1-2 mL / h, and the spinning time is 5-12 h.

[0015] In step 1), the heat treatment temperature is 200-500°C, preferably 350-450°C. The annealing time is 0.5-24 hours, preferably 1-4 hours. The heating rate is 1-20°C / min. Preferably 5-10°C / min.

[0016] Step 1) The heat treatment atmosphere is at least one of air, oxygen, nitrogen, argon and carbon dioxide.

[0017] In step 2), the alkaline solution is one or more solutions of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, etc. Preferably, the alkaline solution is one or more solutions of sodium hydroxide and potassium hydroxide.

[0018] In the above technical solution, the alkaline solution reopens the amide bond of the polyimide and replaces the hydrogen of the hydroxyl group with an alkaline metal element under alkaline conditions. Then, through ion exchange, the alkaline metal element is converted into the target metal to form a stronger chemical bond.

[0019] In step 2), the solvent of the alkaline solution is at least one of water, methanol and ethanol. The molar concentration of the alkaline solution is 0.001-10 mol / L, preferably 0.01-1 mol / L, and more preferably 0.01-0.1 mol / L. The temperature of the alkaline solution is 0-100° C., preferably 30-60° C. The soaking time is 0.1-12 hours, preferably 0.5-5 hours.

[0020] The present invention can customize the depth of polyimide ring opening on the fiber surface, that is, the subsequent metal loading amount and loading depth, by accurately controlling the alkaline solution concentration, solution temperature, and placement time.

[0021] In step 2), the solvent of the salt solution is at least one of water, methanol and ethanol. The molar concentration of the salt solution is 0.001-10 mol / L, preferably 0.01-1 mol / L, and more preferably 0.01-0.1 mol / L.

[0022] In step 2), the salt solution is a metal salt solution, and the metal salt is any one of Mg, Al, Si, Ca, Sc, Fe, Co, Ni, Cu, Zn, Ge, Se, Ag, In, Sn, Pt, Au, and Bi.

[0023] Preferably, it is a salt of any one of Mg, Al, Si, Ca, Sc, Zn, Ge, Se, Ag, In, Sn, Pt, Au, and Bi. More preferably, it is a salt of any one of Mg, Al, Ca, Zn, and Ag.

[0024] In step 3), the heating rate during high temperature treatment is 1-20°C / min, preferably 3-5°C / min. The temperature of high temperature treatment is preferably 700-1500°C, more preferably 800-1000°C. The high temperature treatment time is preferably 1-5 hours.

[0025] Preferably, the inert atmosphere is any one of hydrogen, ammonia, nitrogen, argon and carbon dioxide.

[0026] The method of the present invention can prepare a negative electrode material with a controllable metal loading depth, wherein the negative electrode material has a metal surface with lithium-philic activity exposed, which can reduce the lithium ion diffusion path and achieve uniform deposition of metallic lithium. The negative electrode material with a controllable metal loading depth can be used in alkali metal batteries, such as lithium metal batteries.

[0027] Beneficial effects of the present invention:

[0028] 1) The preparation method of the present invention can achieve efficient exposure of metal compounds and significantly promote the performance of lithium metal batteries. The structural design of the present invention greatly shortens the diffusion distance of lithium ions between the electrolyte and the negative electrode material, effectively reduces the internal resistance of the battery, and improves the migration rate and utilization rate of lithium ions. This feature is crucial to improving the overall charge and discharge performance of lithium metal batteries, allowing the battery to maintain high energy conversion efficiency and stability during rapid charge and discharge, meeting the urgent needs of electronic devices for high-power, high-energy density battery systems.

[0029] 2) The preparation method of the present invention can stabilize the connection mechanism and enhance the conductivity and structural stability. Different from the traditional physical adsorption or simple coating method, the negative electrode material in the present invention forms a stable chemical bond with a certain thickness between the metal compound and the substrate through a specific chemical reaction. This connection not only enhances the overall conductivity of the negative electrode material, making the electron transmission inside the material smoother, but also improves the structural stability of the material during the charge and discharge cycle. The thick connection layer can effectively resist the growth of lithium dendrites, reduce the risk of short circuits, extend the service life of the battery, and provide a strong guarantee for the safety and reliability of lithium metal batteries.

[0030] 3) The preparation method of the present invention can achieve fine control and promote the industrialization process. The preparation method of the negative electrode material of the present invention combines the essence of fine chemical synthesis and material engineering, and realizes the precise control of the load amount and load depth. The method has standardized steps, is easy to operate, and has a high degree of scalability, which provides the possibility for large-scale industrial production. By adjusting the process parameters, the microstructure and performance of the negative electrode material can be flexibly adjusted to meet the specific requirements for the performance of lithium metal batteries in different application scenarios. In addition, the prepared negative electrode material not only exhibits excellent mechanical properties and can withstand volume changes during the operation of the battery, but also achieves a breakthrough in lithium storage performance, reaching the development standard of high-energy-density lithium metal batteries for high-specific-capacity metal lithium negative electrodes, injecting new vitality into the development of the new energy field. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A flow chart of a method for preparing a negative electrode material according to an embodiment of the present invention;

[0032] Figure 2 This is a transmission electron microscopy image of an ultrathin section of nanofibers loaded on a metal surface prepared in Example 1 of the present invention;

[0033] Figure 3 This is a transmission electron microscopy image of an ultrathin section of nanofibers loaded on a metal surface prepared in Example 2 of the present invention;

[0034] Figure 4 This is a transmission electron microscopy image of an ultrathin section of nanofibers loaded on a metal surface prepared in Example 3 of the present invention;

[0035] Figure 5 This is a transmission electron micrograph of an ultrathin section of nanofibers loaded on a metal surface prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0036] Lithium metal, with its excellent theoretical capacity (up to 3860mAh / g) and extremely low density (only 0.53g / cm 3) and extremely negative potential (-3.04V relative to standard hydrogen electrode (SHE), are considered to be ideal candidates for constructing the next generation of high energy density secondary battery anode materials. However, the uncontrolled growth of lithium dendrites, low Coulombic efficiency and the resulting safety hazards have severely restricted the widespread application of lithium metal anodes in the field of rechargeable batteries. To overcome these challenges, three-dimensional (3D) porous current collectors have emerged, which show significant advantages in inhibiting lithium dendrite formation and improving Coulombic efficiency by significantly reducing the effective current density. In this context, materials such as graphene, carbon fiber, copper foam and nickel foam have been widely explored as preferred matrices for lithium deposition due to their unique physical and chemical properties. In order to further reduce the polarization phenomenon during nucleation and deposition, researchers are committed to incorporating various composite materials into these matrices to enhance their affinity for lithium metal. Specifically, the introduction of innovative materials such as nitrogen-doped graphene, ZnO quantum dots and Ag nanocrystals not only effectively reduces the nucleation overpotential, but also promotes the smooth progress of the nucleation process, thereby achieving a uniform distribution of lithium nuclei. These 3D negative electrode materials rich in lithium-philic particles or functional groups provide strong support for the uniform deposition of lithium. However, it is worth noting that for lithium-philic substances embedded in the matrix, their complex diffusion paths may constitute additional diffusion barriers, thereby inducing the re-formation of lithium dendrites. Therefore, designing a 3D main structure that can efficiently expose active sites and promote uniform diffusion and deposition of lithium ions has become the key to improving the safety and performance of lithium metal batteries. Through such innovative designs, we hope to overcome existing difficulties and promote the commercialization of lithium metal anode technology in the field of rechargeable batteries.

[0037] In view of this, the present invention provides a method for preparing a negative electrode material with controllable metal loading depth. The negative electrode material prepared by this method has the characteristics of controllable metal loading amount and depth, and the exposure of metal particles can more directly induce the controllable deposition of lithium ions on the surface of the negative electrode material, effectively improving the cycle stability of lithium metal batteries.

[0038] The flow chart of the preparation method of the present invention is as follows Figure 1As shown, it includes the steps of S101 preparing nanofiber membrane, S102 surface treatment loading metal elements, and S103 high-temperature heat treatment to reduce metal. Specifically, the preparation method of the present invention includes the following key steps: A. Preparation of polyamic acid nanofiber membrane: First, a polyamic acid nanofiber membrane is prepared by preparing a polyamic acid solution and utilizing electrospinning technology, followed by heat treatment to convert it into a polyimide nanofiber membrane. B. Surface modification: The polyimide nanofiber membrane is immersed in an alkaline solution for surface hydrolysis to open the ring structure and enhance the reactivity of the membrane with metal salts. After washing, the membrane is immersed in a metal salt solution for chemical reaction, and then washed and dried. C. Metal particle loading: The metal salt-loaded nanofiber membrane is subjected to high-temperature heat treatment, and by precisely controlling the heat treatment conditions, the uniform loading of metal particles on the surface of the nanofiber membrane is achieved, thereby obtaining a nanofiber membrane with a controllable loading depth.

[0039] In the embodiment of the present invention, through the realization of a series of fine chemical control steps, the preparation method provided has standardized steps and is convenient for large-scale production. The negative electrode material has a deeply controllable metal loading, can accurately control the loading amount of the metal active substance, and the particles are concentrated in the surface layer, which can maximize the exposure of active sites and induce lithium deposition. The present invention aims to provide a material with excellent mechanical properties, light weight and lithium storage performance.

[0040] Among them, a polyamic acid nanofiber membrane is prepared by preparing a polyamic acid solution and using an electrostatic spinning technique, and then heat-treated to convert it into a polyimide nanofiber membrane. The polyimide nanofiber membrane is immersed in an alkaline solution for surface hydrolysis to open the ring structure and enhance the reactivity of the membrane with the metal salt. After washing, the membrane is immersed in a metal salt solution for chemical reaction, and then washed and dried. The metal salt-loaded nanofiber membrane is subjected to high-temperature heat treatment, and by precisely controlling the heat treatment conditions, the uniform loading of metal particles on the surface of the nanofiber membrane is achieved, thereby obtaining a nanofiber membrane with a controllable loading depth.

[0041] Example 1

[0042] The method for preparing the negative electrode material with controllable metal loading depth of this embodiment comprises the following steps:

[0043] 1) Using N,N-dimethylacetamide (DMAc) as a solvent, a polyamic acid solution with a mass fraction of 20% was prepared. The polyamic acid solution was used as a spinning solution for electrospinning, and a nanofiber membrane was uniformly deposited on an aluminum foil substrate under the conditions of a spinning voltage of 18 kV, a receiving distance of 15 cm, and a spinning solution flow rate of 1 mL / h. The spinning time was 12 hours.

[0044] The temperature was slowly raised to 400° C. at a rate of 5° C. / min in an air environment and kept at that temperature for 1 hour for annealing treatment to obtain a polyimide nanofiber membrane.

[0045] 2) The polyimide nanofiber membrane prepared in step 1) was immersed in a 0.1 mol / L (M) KOH aqueous solution at 40°C for 1 hour for soaking treatment; the membrane was taken out and rinsed with deionized water to remove residual KOH. The fiber membrane was then immersed in a 0.1M AgNO3 aqueous solution at 30°C for 30 minutes, taken out and rinsed with deionized water, and dried naturally at room temperature overnight.

[0046] 3) The treated nanofibers are placed in an argon protective atmosphere and heated to 900°C at a heating rate of 3°C / min and kept at this temperature for 1 hour to obtain a negative electrode material with controllable metal loading depth.

[0047] Example 2

[0048] The only difference between Example 2 and Example 1 is that the surface activation treatment time in step 2) is 2 hours.

[0049] Example 3

[0050] The only difference between Example 3 and Example 1 is that the surface activation treatment time in step 2) is 5 hours.

[0051] Example 4

[0052] The only difference between Example 4 and Example 1 is that in step 2), the polyimide nanofiber membrane is immersed in a 1M KOH aqueous solution at 50° C. for 1 hour.

[0053] Example 5

[0054] The only difference between Example 5 and Example 1 is that in step 2), the polyimide nanofiber membrane is immersed in a 1M KOH aqueous solution at 30° C. for 1 hour.

[0055] Example 6

[0056] The only difference between Example 5 and Example 1 is that in step 2), the polyimide nanofiber membrane is immersed in a 0.01M KOH aqueous solution at 30° C. for 5 hours.

[0057] Example 7

[0058] The only difference between Example 7 and Example 2 is that the AgNO3 aqueous solution in step 2) is replaced by Al(NO3)3 solution.

[0059] Example 8

[0060] The only difference between Example 8 and Example 2 is that the AgNO3 aqueous solution in step 2) is replaced by MgCl2 solution.

[0061] Example 9

[0062] The difference between Example 9 and Example 2 is that the AgNO3 aqueous solution in step 2) is replaced by a mixed solution of Zn(NO3)2 and AgNO3, and the temperature of the high temperature treatment in step 3) is 800°C. The mixed solution of Zn(NO3)2 and AgNO3 is prepared by mixing Zn(NO3)2 and AgNO3 in a molar ratio of 1:8 and dissolving them in water. The rest is the same as in Example 2.

[0063] Comparative Example 1

[0064] The difference between Comparative Example 1 and Example 1 is that no alkaline solution is used for soaking treatment.

[0065] Comparative Example 2

[0066] The difference between Comparative Example 2 and Example 1 is that the metal element is directly loaded into the fiber membrane through a one-step electrospinning process. The specific preparation steps are as follows:

[0067] Preparation of metal-loaded polyimide nanofiber membrane. Prepare a polyamic acid solution with a mass concentration of 20wt%, using N,N-dimethylacetamide (DMAc) as a solvent. Subsequently, add 2wt% AgNO3 to the solution. Using electrospinning technology, under the conditions of a set spinning voltage of 20kV, a receiving distance of 15cm, and a spinning solution flow rate of 1mL / h, the mixed solution is evenly spun on an aluminum foil substrate to form a nanofiber membrane. The spinning process lasts for 12 hours. Afterwards, heat treatment is performed, that is, slowly heating to 900℃ at a rate of 3℃ / min in an argon atmosphere, and maintaining this temperature for 1 hour for annealing treatment, and finally a metal-loaded nanofiber membrane is obtained.

[0068] Comparative Example 3

[0069] The only difference between Comparative Example 1 and Comparative Example 2 is that the mass fraction of the added AgNO3 is 4wt%.

[0070] Comparative Example 4

[0071] The only difference between Comparative Example 1 and Comparative Example 2 is that the mass fraction of the added AgNO3 is 10wt%.

[0072] Experimental example

[0073] (1) Morphology test

[0074] The materials obtained in Examples 1-4 were tested by transmission electron microscopy, and the results were as follows:

[0075] Figure 2 This is a transmission electron microscope image of an ultra-thin section of nanofibers loaded on a metal surface prepared in Example 1. It can be seen from the image that a large number of particles are loaded on the surface of the fiber with a diameter of about 500 μm, and from the cross section it can be seen that the particles are only distributed on the outside of the fiber, with a thickness of about 29 nm.

[0076] Figure 3 This is a transmission electron microscope image of an ultrathin section of metal-surface-loaded nanofibers prepared in Example 2. It can be seen from the image that a large number of particles are loaded on the surface of the fiber with a diameter of about 500 μm, and from the cross section, it can be seen that the particles are only distributed on the outside of the fiber, with a thickness of about 51 nm.

[0077] Figure 4 This is a transmission electron microscopy image of an ultrathin section of metal surface-loaded nanofibers prepared in Example 3. It can be seen from the image that the fibers are completely loaded with particles both on the surface and inside.

[0078] Figure 5 This is a transmission electron microscopy image of an ultrathin section of metal-loaded nanofibers prepared in Comparative Example 3. It can be seen from the image that the particles are irregularly distributed in the fibers.

[0079] (2) Charge and discharge test

[0080] The nanofiber membranes prepared in Examples 1-9 and Comparative Examples 1-4 were assembled into symmetrical cells for testing. 2 The current density and 1 mAh / cm 2 The charge and discharge cycle test was carried out under the area capacity. The test results are shown in Table 1. Table 1 also lists the metal loading amount and loading depth.

[0081] Table 1

[0082] Metal Loading amount / wt% Load depth / nm Cycle life / h Example 1 Ag 15% 29 810 Example 2 Ag 22% 51 1494 Example 3 Ag 49% 248 1240 Example 4 Ag 56% 255 1139 Example 5 Ag 55% 245 1352 Example 6 Ag 3% 10 134 Example 7 Al 8% 35 740 Example 8 Mg 6% 32 788 Example 9 Ag+ZnO 19% 50 1531 Comparative Example 1 Ag 7% irregular 155 Comparative Example 2 Ag 11% irregular 214 Comparative Example 3 Ag 18% irregular 398 Comparative Example 4 Ag 35% irregular 510

[0083] It can be seen from the test results in Table 1 that the steps provided in the embodiments of the present invention successfully prepare negative electrode materials with controllable metal loading depth. The metal loading amount and loading depth are regulated by the parameters of the alkali surface activation treatment, especially the alkali solution temperature, alkali solution concentration and immersion time. However, the traditional adsorption method used in Comparative Example 1 cannot effectively load, and the one-step electrospinning method used in Comparative Examples 2-4 cannot form nanofibers with controllable metal loading depth. In addition, the battery cycle life of Examples 1-5 and Examples 7-8 is significantly improved compared to Comparative Examples 1-4, indicating that the nanofiber film loaded on the metal surface greatly improves the performance of lithium metal batteries. In summary, the present invention provides a negative electrode material and a preparation method thereof, characterized in that the negative electrode material has a negative electrode material with a controllable metal loading depth, and its application in lithium metal batteries can obtain improved electrochemical performance.

Claims

1. A method for preparing a nanofiber membrane with controllable metal loading depth, characterized in that: The steps include: 1) electrospinning a polyamic acid solution, and heat treating and annealing the obtained membrane to obtain a nanofiber membrane; 2) soaking the prepared nanofiber membrane in an alkaline solution for 0.5-3 hours, then soaking it in a salt solution at 25-45°C for 10-50 minutes, and drying it; The salt solution is a solution of one or more of metal hydrochloride, metal nitrate, metal sulfate, and metal carbonate; 3) The nanofiber membrane obtained by drying in step 2) is treated at a high temperature of 200-3000° C. for 0.5-24 h under an inert atmosphere to obtain the nanofiber membrane.

2. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 1, characterized in that: The mass concentration of the polyimide acid solution in step 1) is 1-50wt%.

3. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 1, characterized in that: The heat treatment temperature in step 1) is 200-500°C.

4. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 3, characterized in that: The atmosphere of step 1) heat treatment is at least one of air, oxygen, nitrogen, argon and carbon dioxide.

5. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 1, characterized in that: In step 2), the alkaline solution is one or more solutions of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, etc.

6. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 1, characterized in that: The molar concentration of the salt solution is 0.001-10 mol / L.

7. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 1, characterized in that: In step 2), the salt solution is a metal salt solution, and the metal salt is any one of Mg, Al, Si, Ca, Sc, Fe, Co, Ni, Cu, Zn, Ge, Se, Ag, In, Sn, Pt, Au, and Bi.

8. The method for preparing a nanofiber membrane with controllable metal loading depth according to claim 1, characterized in that: The metal salt is a mixture of silver nitrate and zinc nitrate.

9. A nanofiber membrane with controllable metal loading depth obtained by the preparation method as claimed in claim 1.

10. A lithium metal battery, comprising a housing and a positive electrode and a negative electrode disposed in the housing, wherein the negative electrode comprises a negative electrode material, characterized in that: The negative electrode material adopts the nanofiber membrane with controllable metal loading depth as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of composite lithium metal anode

    CN108365200A

  • Preparation method of cross-linked polyimide fiber membrane

    CN108755144A

  • A surface dendrite-free high-safety metal lithium anode and preparation method and application thereof

    CN109088051A

  • Surface lithiated polyimide film as well as preparation method and application thereof

    CN117996349A

  • PI (Polyimide) nanofiber composite membrane with lithium dendrite inhibiting function as well as preparation and application of PI nanofiber composite membrane

    CN118554122A